The long odyssey for the DEE‐CDKL5 diagnosis: A call for action - Kette D. Valente; Fernanda Melo; Rachel Marin; Gustavo Vega; Ana Neves‐Borg; Bianca Spagnol; Maria Augusta Montenegro; Silvia Vincentiis (Epilepsia Open)
Abstract Objectives This study aims to determine the current state of CDD diagnosis and epilepsy treatment in an upper‐middle‐income country. Methods Forty‐seven families of the Brazilian CDD Association were invited to participate in an online survey to gather information about the diagnosis and treatment of epilepsy. Results Forty‐three families (91.5%) of unrelated patients with confirmed genetic diagnosis of CDD participated. The median age was 7 years (ranging from 1.3–25 years) and the male: female ratio was 1:6. Early and severe epilepsy started during infancy in 74.4%. Seizures occurred daily in 61.9% and 83.7% had clusters of seizures. The mean age of diagnosis was 3.3 years (ranging from 37 days to 16 years), and younger patients had an earlier diagnosis (p < 0.001). Patients were seen by an average of 4.4 physicians (1–15) before the diagnosis. The most relevant obstacles to genetic testing were cost (55.8%) and late requests by physicians (27.9%). At the moment of the assessment, patients received a mean of 3.6 ASMs/day (ranging from 1 to 5). Thirty‐four (79.1%) caregivers reported side effects throughout life, including life‐threatening events in 16.3%. Significance Based on our findings, a sense of urgency for genetic assessment implementation is evident since the delay in the diagnosis with unnecessary use of resources and excessive polytherapy with serious side effects cause a higher burden to the healthcare system, caregivers, and patients. Plain Language Summary In this study, we assessed the diagnosis and treatment of patients with genetically confirmed DEE‐CDKL5 from the Brazilian Association of CDD with an online survey. Caregivers reported a long delay in the diagnosis associated with cost and late referral to genetic testing, considered the last resource for one‐third of the patients. Patients received a high number of ASM, mainly under polytherapy, with serious side effects. Although it is promising that younger patients received earlier diagnosis, public policies for genetic testing are needed to improve CDD patients' care.